Reversion SAMD9 Mutations Modifying Phenotypic Expression of MIRAGE Syndrome and Allowing Inheritance in a Usually de novo Disorder - Roucher-Boulez, Florence; Mallet, Delphine; Chatron, Nicolas; Dijoud, Frédérique; Gorduza, Daniela Brindusa; Bretones, Patricia; Morel, Yves (Frontiers in Endocrinology, 2019)
Context: MIRAGE (Myelodysplasia, Infection, Restriction of growth, Adrenal hypoplasia, Genital phenotypes, Enteropathy) syndrome is a severe multisystem disorder with high mortality. It is caused by a heterozygous gain of function mutation in the growth repressor gene SAMD9. The increasing number of reported cases displays a spectrum of phenotypes that may be explained by an adaptation mechanism,with appearance of a somatic second hit mutation with revertant effects. Objective: To determine the genetic basis of the MIRAGE syndrome rapidly corrected in a living and healthy 46,XY patient. Subjects and Methods : A 46,XY patient born with growth restriction and disorders of sex development had thrombocytopenia and necrotizing enterocolitis during the neonatal period suggestive of the syndrome. Faced with the rapid improvement of the patient’s phenotype, an adaptation mechanism was sought by repeating genetic analysis at different ages; her parents also underwent genetic analysis. Results: The previously described p.(Thr778Ile) mutation was identified and surprisingly transmitted by the asymptomatic mother in this usually de novo syndrome. To explain the rapid improvement of the patient’s phenotype and absence of symptoms in the mother, an adaptation mechanism was sought. For the mother, a nonsense mutation was found (p.(Arg221*)) in cis, and most likely appeared in utero. It was not transmitted to her child. The child harboured a different non sense mutation (p.(Arg285*)) that most likely appeared near day 20. Conclusions: We show that pathogenic variants can be inherited from a healthy parent as the adaptation mechanism may arise early in life and mask symptoms. Presence of revertant mosaicism mutations could explain ‘incomplete penetrance’ in other disease. For a better management and outcomes in patients, appearance of this natural gene therapy should be sought by repeating genetic analysis.